An assessment of operations of selected fastfood chains in Western Visayas - Lucero, Marcelo Chavez, Jr (Danyag :the UPV journal of humanities and social sciences, 2004)
"This study was conducted to assess the operations of Jollibee, Chowking and Greenwich in Western Visayas. It delved on five areas: (1) the efficiency of these fastfood chains as perceived by its Managers based on five variables (5P's) which are people, plants, parts, processes and planning & control; (2) customers' satisfaction based on the five areas of operations which are price, service, product quality, facilities and location; (3) the significant difference in the level of efficiency among the three fastfood chians in the areas of the 4P's; (4) the significant difference in the level of customers' satisfaction among the fastfood chains in the five areas of operations; and (5) the significant relationship between the efficiency and customers' satisfaction of each aforementioned fastfood chains."